EFFECT OF DIFFERENT THERAPIES IN EARLY POST PARTUM PERIOD ON FERTILITY OF HF COWS - MISHRA, G K; Derashrl, H J; SARVAIYA, N P; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
This study was conducted on 24 normally calved HF cows of university farm divided into fourgroups; each of six animals. Group I served as control-- only Al; whereas Group It was treated withOxytetracycline (2 g Uroblex ob let) intrauterine on 2nd day postpartum after expulsion of placentc:1 +GnRH (lnj. Receptal) 50th day postpartum+ Al; Group Ill - Oxytetracycline + GnRH + Herbal Bolus(Bioheat) orally 50111 day postpartum +Aland Group IV - Oxytetracycline + GnRH + non-surgical ET 71hday post~estrus. The overall mean levels of plasma progesterone, glucose, total protein, total cholesteroland total triglycerides on 501r, day postpartum were 1.80 ± 0.46 ng/m/, 32.54 ± 5.48 mg/di, 4.48 ± 0.41g/dl, 57.09 ± 8.88 mg/di and 182.96 ± 20.56 mg/di, respectively. Significant differences (P < 0.05) wereobserved between groups for plasma P4 and triglycerides levels. The level of progesterone in controlgroup was significantly higher than the treatment group (3.25 ± 1.31 vs 1.32 ± 0.41 ng/ml). Controlgroup showed significant variation from the treatment groups for most metabolites, but within thetreatment groups there was no significant variation. Percentage of animals conceived in control andtreatment groups were 33.33, 83.33, 100.00 and 50.00, respectively. The pooled conception rate of alltreatment groups [77.78% (14i18)J was higher than the control group [33.33% (2/6)]. The animals oftreatment group having lower plasma prog0stercne concentration on 5Q1h day postpartum respondedwell to the hormonal (GnRH) and herbal (Bioheat) treatments and had better conception rates than thecontrol group. The animals having higher blood glucose and lower triglycerides concentration alsoconceived earlier.
Keywords: HF cows; Plasma metabolites; Progesterone concentration; Postpartum fertility